Few-shot learning approach with multi-scale feature fusion and attention for plant disease recognition - Lin, Hong; Tse, Rita; Tang, Su-Kit; Qiang, Zhen-ping; Pau, Giovanni (Frontiers in Plant Science, 2022)
Image-based deep learning method for plant disease diagnosing is promising but relies on large-scale dataset. Currently, the shortage of data has become an obstacle to leverage deep learning methods. Few-shot Learning can generalize to new categories with the supports of few samples, which is very helpful for those plant disease categories where only few samples are available. However, two challenging problems are existing in Few-shot Learning: 1) the feature extracted from few shots is very limited; 2) generalizing to new categories, especially to another domain is very tough. In response to the two issues, we propose a network based on the Meta-Baseline few-shot learning method, and combine Cascaded Multi-scale Features and Channel Attention. The network takes advantage of Multi-scale Features to rich the feature representation, uses Channel Attention as a compensation module efficiently to learn more from the significant channels of the fused features. Meanwhile, we propose a group of training strategies from data configuration perspective to match various generalization requirements. Through extensive experiments, it is verified that the combination of Multi-scale Feature Fusion and Channel Attention can alleviate the problem of limited features caused by few shots. To imitate different generalization scenarios, we set different data settings and suggest the optimal training strategies for Intra-domain case and Cross-domain case, respectively. The effects of important factors in few-shot learning paradigm are analyzed. With the optimal configuration, the accuracy of 1-shot task and 5-shot task achieve at 61.24% and 77.43% respectively in the task targeting to single-plant, and achieve at 82.52% and 92.83% in the task targeting to multi-plants. Our results outperform the existing related works. It demonstrates that the few-shot learning is a feasible potential solution for plant disease recognition in the future application.